Balloon-expandable transapical transcatheter aortic valve implantation with or without predilation of the aortic valve: results of a multicentre registry. (22nd November 2017) - Strauch, Justus; Wendt, Daniel; Diegeler, Anno; Heimeshoff, Martin; Hofmann, Steffen; Holzhey, David; Oertel, Frank; Wahlers, Thorsten; Kurucova, Jana; Thoenes, Martin; Deutsch, Cornelia; Bramlage, Peter; et al.
Abstract: OBJECTIVES: To assess safety and efficacy of transapical transcatheter aortic valve implantation (TA-TAVI) in the absence of predilation using balloon aortic valvuloplasty (BAV). Predilation of the stenosed valve using BAV is a routine step in TA-TAVI; however, evidence supporting its clinical value is lacking, and several studies have linked it with higher complication rates. METHODS: A prospective, two-armed, multicentre registry (EASE-IT TA) to gather data on patients undergoing TA-TAVI with or without BAV, using the Edwards SAPIEN 3 valve was designed. The primary evaluation criterion was a composite of all-cause mortality, non-fatal stroke, non-fatal myocardial infarction, acute kidney injury and pacemaker implantation [per Valve Academic Research Consortium-2 (VARC-2)] within 30 days after TAVI. RESULTS: A total of 198 subjects underwent TA-TAVI, 61 with and 137 without BAV. Patient characteristics were comparable at baseline (mean ± SD: age 80.3 ± 5.7 years; logistic EuroSCORE 20.2 ± 12.6). Similar reductions in peak and mean transvalvular gradients were observed post-procedurally. There was a significant reduction of fluoroscopy time without BAV (4.7 vs 7.9 min; P  = 0.039) and significantly decreased odds of catecholamine administration (17.5% vs 32.8%; P  = 0.017). A decreased odds of the primary evaluation criterion in patients without BAV after 30 days (adjusted odds ratio 0.71; 95% confidence interval 0.34–1.82) and the same composite end-point after 6 months (adjusted odds ratio 0.74; 95% confidence interval 0.37–1.47) were not significant even after multivariable adjustment. CONCLUSIONS: TA-TAVI without BAV appears to be at least equal to its conventional counterpart in terms of efficacy and may offer advantages in terms of safety. Thus, there appears to be little justification for maintaining the BAV step in TA-TAVI for many patients.